Impact of Outlet Pressure on Internal Flow Characteristics and Energy Loss in Pump-Turbine System Under Pump Operation Conditions - Tianding Han; Qifei Li; Licheng Feng; Xiangyu Chen; Feng Zhou; Zhenggui Li (Energies)
During pump operation, the pump-turbine system experiences unstable fluctuations in outlet pressure, which induces turbulence and additional energy losses. Understanding the impact of outlet pressure variations on the internal flow field is crucial for the further development of turbine units. This study employs numerical methods to systematically analyze the effects of outlet pressure changes on flow characteristics and energy loss. The results show that a decrease in outlet pressure to P0.9BEP significantly increases entropy production in the double-row stay guide vane region, primarily due to flow separation and vortex formation. In the flow passage, sealing gap, and tailpipe regions, entropy production is mainly driven by wall effects, while secondary flows influence the spiral case. The vortex distribution in the double-row stay guide vane is complex, with different variation trends observed in the active and fixed guide vane regions. Outlet pressure changes affect the interaction between the flow passage blades and the fluid, leading to localized flow separation and directly impacting energy loss in downstream components. Additionally, the rate of change in outlet pressure significantly influences vortex generation and dissipation. This research provides new theoretical insights and research directions for performance optimization and energy loss control in pump-turbine systems.